ABCC5 and ABCG1 polymorphisms predict irinotecan-induced severe toxicity in metastatic colorectal cancer patients. Issue 12 (December 2015) - Chen, Sylvia; Villeneuve, Lyne; Jonker, Derek; Couture, Félix; Laverdière, Isabelle; Cecchin, Erica; Innocenti, Federico; Toffoli, Giuseppe; Lévesque, Eric; Guillemette, Chantal
Abstract : Objective: Irinotecan is a cytotoxic agent used widely for the treatment of solid tumors, particularly for metastatic colorectal cancers. Treatment with this drug frequently results in severe neutropenia and diarrhea that can markedly impact the course of treatment and patients' quality of life. Pharmacogenomic tailoring of irinotecan-based chemotherapy has been the subject of several investigations, but with limited data on ATP-binding cassette ( ABC ) and solute carrier ( SLC ) transporter genes. Materials and methods: In this study, we aimed to discover toxicity-associated markers in seven transporter genes participating in irinotecan pharmacokinetics involving the ABC transporter genes ABCB1, ABCC1, ABCC2, ABCC5, ABCG1, and ABCG2 and the solute carrier organic anion transporter gene SLCO1B1 and using a haplotype-tagging single-nucleotide polymorphisms ( n =210 htSNPs) strategy. The profiles of 167 metastatic colorectal cancer Canadian patients treated with FOLFIRI-based regimens were examined and the findings were replicated in an independent cohort of 250 Italian patients. Results: In combined cohorts, a two-marker ABCC5 rs3749438 and rs10937158 haplotype (T–C) predicted lower risk of severe diarrhea [odds ratio (OR) of 0.43; P =0.001]. The co-occurrence of ABCG1 rs225440T and ABCC5 rs2292997A predicted the risk of severe neutropenia (OR=5.93; P =0.0002), which was further improved when incorporating the well-known risk marker UGT1A1 * 28 rs8175347 (OR=7.68; P <0.0001). In contrast, carriers of one protective marker ( UGT1 rs11563250G) but none of these risk alleles experienced significantly less severe neutropenia (8.2 vs. 34.0%; P <0.0001). Conclusion: This combination of predictive genetic markers could potentially lead to better risk assessment and may thus improve personalized treatment. Abstract : Supplemental Digital Content is available in the text.